Pengendalian Konsumsi Gula Dalam Mencegah Penyakit Diabetes Melitus Tipe II Di Usia Dini - Lestari, Trisna; Bachtiar, Arsyad; Kurniawa, Agus; Feyki, Della Fitrian; Melina, Melina; Fitri, Aisyah Nur; Baqiyatusshalihah, Ratu Binar; Rizky, Muhammad; Audriana, Reza; Luthfiah, Ade Sofi; Dipriana, Dipriana (Abdi Geomedisains, 2025)
Diabetes Mellitus (DM) is a chronic disease caused by a lack of insulin production or resistance to insulin, which leads to increased glucose levels in the body. This disease has an increasing prevalence, both in developed and developing countries, and is becoming a global health problem. One of the main factors at risk of increasing DM is lifestyle and habits, especially the habit of consuming sweet foods and lack of physical activity. This research aims to provide education about controlling sugar consumption in preventing Type II Diabetes Mellitus at an early age, with a focus on PMR MTSN 1 Cirebon students. The method used is direct outreach in the form of counseling with presentations using PPT and LCD. This research used convenience sampling techniques and involved 36 students as respondents. Data collection was carried out through pretest and posttest with a questionnaire containing 10 questions to assess knowledge about DM and the impact of excessive sugar consumption. The data obtained were analyzed using the Paired t-Test with IBM SPSS Statistics Version 17.0 software to determine differences in knowledge before and after counseling. It is hoped that the results of the research will increase teenagers' awareness of the importance of a healthy lifestyle, especially in controlling sugar consumption, in order to prevent Type II Diabetes Mellitus.